Future Growth, Financial Inclusion and Asia - LEE, David Kuo Chuen (Institutional Knowledge at Singapore Management University, 2015)
How can businesses, entrepreneurs & engineers harness technology and practice inclusiveness to generate revenue and cater to an under-served Asia especially ASEAN? Tapping on Silicon Valley resources and large technology companies in China, do you recognise these opportunities?